OPTIMALISASI MANAJEMEN PELAKSANAAN BIMBINGAN DAN KONSELING LAYANAN KONSULTASI DAN LAYANAN AHLI TANGAN SECARA LANGSUNG DI SEKOLAH - Maulana Riqfi Zaein (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study discusses the optimization of the management of the implementation of guidance and counseling (BK) in schools, with a focus on consultation services and direct case transfer. Guidance and counseling are crucial components in education that aim to help students develop their potential and overcome various problems they face. Effective BK management includes several aspects, namely planning, implementation, and evaluation. The availability of adequate facilities and infrastructure greatly influences the effectiveness of BK services. The purpose of this study shows that if the facilities and infrastructure are inadequate, then BK services will be hampered, while appropriate fulfillment can improve the quality of services and provide significant benefits for student development. The method used is qualitative with literature studies. Literature studies are a way to solve problems by tracing previously written sources. In other words, the term literature study is also very familiar with the term library study. The results of the study indicate that the concept of data collection management used in schools can help optimize counseling services. In this study, the method used was literature study. The results obtained from this study were an increase in the quality of counseling services, an increase in students' understanding of the problems they face, and an increase in students' ability to overcome these problems. The benefits of this study are to improve the quality of education in the school, help students in dealing with personal problems, and improve the relationship between students, teachers, and parents. Therefore, it is recommended that the school can improve the use of student personal books and information brochures for students related to counseling services, and continue to develop the concept of data collection management for optimizing counseling services in the future. Consultation services and experts in the management of BK directly in schools are also very important and can achieve goals effectively which aim to help students overcome problems related to personal, social, learning, and career life, and experts in supporting activities of guidance and counseling involving the transfer of cases to more competent parties if the problem requires special handling. The discussion in this article is Optimizing the Management of the Implementation of Guidance and Counseling services consultation and experts directly in schools Using qualitative research methods, this study investigates the effectiveness of BK management directly in schools, the importance of optimizing consultation services and experts in the management of BK in schools.